A new species and two new species records of Hierodulinae from China, with a revision of Hierodula chinensis (Mantodea: Mantidae). (2nd January 2021) - Liu, Qin-Peng; Liu, Zi-Jun; Chen, Zhi-Teng; Yuan, Zhong-Lin; Shi, Yan
ABSTRACT: Hierodula jianfenglingensis sp. nov . (Ledong, Hainan) is described as a new species. Its related taxa, Hierodula chinensis Werner, 1929, is revised herein based on some confusions that exist in previous papers. Hierodula dyaka Westwood, 1889 (Xishuangbanna, Yunnan) is re-described and newly recorded from China. Mekongomantis quinquespinosa Schwarz, Ehrmann, & Shcherbakov, 2018 (Xishuangbanna, Yunnan), a newly recorded genus and species from China, is also re-described. Photographs are provided for all adults, along with the ootheca of H. jianfenglingensis sp. nov . and M. quinquespinosa Schwarz, Ehrmann, & Shcherbakov, 2018. http://www.zoobank.org/urn:lsid:zoobank.org:pub:0c2b54b7-3a7b-4f1b-8241-e9ac293f1cbb